Modern Contraceptive Utilization and Associated Factors among Married Gumuz Women in Metekel Zone North West Ethiopia. (23rd July 2020) - Adane, Alemnew Ashagrie; Bekele, Yibeltal Alemu; Melese, Ergoye; Worku, Getasew Taddesse; Netsere, Henok Biresaw
Abstract : Background . Modern contraceptives are a key intervention to improve the health of both the mother and children by preventing unintended pregnancy. However, significant numbers of women were facing abortion-related morbidity and mortality globally including Ethiopia due to the nonuse or failure of contraceptive uses. Therefore, the aim of this study was to assess the utilization of modern contraceptive methods and associated factors among married Gumuz women in Metekel Zone North West Ethiopia. A community-based cross-sectional study was conducted among 580 women from March 1 to 30/2019. Pretested structured interview administer questionnaires was used to collect the data. Data were cleaned, coded, and entered into Epi-info version 7.1 and export to SPSS for farther analysis. Both bivariate and multivariate analyses were used. On bivariate analysis P value, less than 0.2 were used to select the candidate variable for multivariate analysis. P value and 95% confidence interval were used to measure the level of significance on multivariate analysis and those variables whose P value < 0.05 were considered as statically significant. The prevalence of modern contraceptive method was 18.6% [95% CI: 15.00-22.00]. Age ≥ 35 year AOR 4.67; 95% CI (1.34 -16.18), able to read and write AOR 6.45 95% CI(2.98-13.97), primary school AOR 6.56; 95% CI (2.22-19.38), secondary school AOR 7.27; 95% CI (3.00 -17.61), counseled on contraceptive methods AOR 3.72 95% CI (2.11-6.56), moderate knowledge on modern contraceptive method AOR 2.31; 95% CI (1.15-4.64), and good knowledge on modern contraceptive method AOR 4.37; 95% CI (2.38-8.02) were identified as statistically significant with modern contraceptive methods utilization. The prevalence of contraceptive utilization was low when compared to the national and the regional figure. Maternal age, maternal educational status, counseling about modern contraceptive methods, and knowledge on modern contraceptive methods were found as statistically significant with modern contraceptive utilization.